2006
DOI: 10.2136/sssaj2005.0088
|View full text |Cite
|
Sign up to set email alerts
|

Soil Processes Affected by Sixteen Grassland Species Grown under Different Environmental Conditions

Abstract: Plant species, and their interactions with the environment, determine both the quantity and chemistry of organic matter inputs to soils. Indeed, countless studies have linked the quality of organic matter inputs to litter decomposition rates. However, few studies have examined how variation in the quantity and chemistry of plant inputs, caused by either interspecific differences or changing environmental conditions, influences the dynamics of soil organic matter. We studied the effects of 16 grassland species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
46
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 47 publications
10
46
0
Order By: Relevance
“…Interestingly, plant litter from C 4 grasses typically is of inferior quality (less decomposable) of that from C 3 grasses (e.g. Dijkstra et al, 2006). Litter quality is known to be a key trait that affects N-mineralization (Van der Krift and Berendse, 2001) and consequently other N-cycling processes such as nitrification (Booth et al, 2005).…”
Section: Plant Community Level Shiftsmentioning
confidence: 99%
“…Interestingly, plant litter from C 4 grasses typically is of inferior quality (less decomposable) of that from C 3 grasses (e.g. Dijkstra et al, 2006). Litter quality is known to be a key trait that affects N-mineralization (Van der Krift and Berendse, 2001) and consequently other N-cycling processes such as nitrification (Booth et al, 2005).…”
Section: Plant Community Level Shiftsmentioning
confidence: 99%
“…It is more probable that in undisturbed, northern mixed-grass ecosystems (Coupland, 1992), there is a more equal distribution of cool-season and warm-season grass species. In a reclaimed situation, though warm-season grasses are often seeded into reclaimed sites they are often out competed by cool-season grasses, and cool-season grasses are typically more productive than warm-season grasses (Dijkstra et al, 2006). Finally, reclaimed sites typically have a greater plant density than found on undisturbed, native sites, which leads to greater productivity (G. Schuman, pers.…”
Section: Discussionmentioning
confidence: 99%
“…So it remains to be seen if the net result of climate change will increase or decrease the carbon sink in grassland. Whatever the outcome will be, the room to manipulate here is quite small, although Dijkstra et al (2006) andDe Deyn et al (2011) showed that species richness (with an important role for legumes) continues to be the best guarantee for carbon sequestration.…”
Section: Grazed Grasslandmentioning
confidence: 99%